TINJAUAN HUKUM PEMBERIAN NAFKAH IDDAH PADA PERKARA NOMOR 1954/pdt.g/2019/PA.Btm - Winda Fitri; Muhammad Naufal Anshari; Fariz Rayhan; Regina Uliana Sirait; Dinda Lucida Siswan (Institut Nalanda, 2023)
This study discusses how to analyze the judge's decision on divorce in decision number 1954/pdt.g/2019/PA.Btm. then analyze the judge's decision to determine the cost of iddah and legal review of the divorce decision. The research method used is a juridical approach method based on legislation on religious courts and complications of Islamic law. Several factors lead to divorce such as differences of opinion, quarrels, arguments and disputes that cause dislike between husband and wife. In preventing divorce, it can be done by mediation, but if it does not find a middle point in the problem between husband and wife, it will proceed to a divorce trial in a religious court.